PENINGKATAN KETERAMPILAN MENULIS CERITA PENDEK DENGAN MENGGUNAKAN MODEL PEMBELAJARAN PROBLEM CENTERED LEARNING (PCL) PADA SISWA KELAS V SD KRISTEN KIERA - Oraplean, Yosina Yokbet; Ririhena, Ribka L.; Kilikily, Cristianti C. (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to find out the improvement in the skill of writing short stories on students of class V SD Kristen Kiera on the material of daily life events using the Problem Centered Learning (PCL) Model. This study is a classroom action research. The location used for this research is SD Kristen Kiera. The subjects of this research are the students of class V SD Kristen Kiera, amounting to 12 students. The improvement in the skill of writing short stories using the Problem Centered Learning (PCL) model occurred in cycle I but has not yet reached its maximum with the lower category, so it was continued to cycle ll, and there was a significant improvement in the very good category.